Hubungan Antara Sikap Terhadap Perilaku Seks Pranikah dengan Perilaku Seks Pranikah pada Mahasiswa - Sara Sola Gratia Naibaho; Ratriana Y . E. Kusumiati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the relationship between students' attitudes toward premarital sex behavior and premarital sex behavior. Using quantitative approaches with correlation methods, this study involved students aged 18-25 years who had or had a partner. The sampling technique used was Accidental Sampling, with respondents as many as 125 students. Premarital sexual behavior was measured using the Guttman scale based on the stages of premarital sexual behavior: touching, kissing, petting, and intercourse. Attitudes toward premarital sex are measured by the Brief Sexual Attitude Scale (BSAS) which includes four dimensions: permissiveness, birth control, communion, and instrumentality. The results showed a positive relationship between attitudes towards premarital sex and premarital sex behavior, with a Pearson correlation coefficient of 0.479 and significant at p<0.05. Attitudes contributed 22.9% to premarital sexual behavior.